Leber’s hereditary optic neuropathy: case report and literature review - Teive, Hélio Afonso Ghizoni; Troiano, André Ribeiro; Raskin, Salmo; Werneck, Lineu César (São Paulo Medical Journal, 2004)
CONTEXT: Leber’s hereditary optic neuropathy is an important cause of progressive painless visual loss among young male patients. OBJECTIVE: To report on a case of a young patient with a clinical and neurophysiological condition suggestive of Leber’s hereditary optic neuropathy, confirmed by genetic testing. CASE REPORT: We describe a 17-year-old male with progressive bilateral visual loss. Two maternal uncles had had similar patterns of visual loss. The patient had a history of smoking and alcohol abuse. Neuro-ophthalmological examination revealed visual acuity of 20/800 in both eyes, with decreased direct and consensual pupillary light reflexes. Fundus examination demonstrated pale optic discs. The visual evoked potential test showed signs of conduction disturbances in both optic nerves and campimetric study showed complete visual loss in all fields of both eyes. A diagnosis of bilateral optic neuropathy with a clinical suspicion of Leber’s hereditary optic neuropathy was made. A blood sample was submitted to genetic analysis in relation to the principal mutations of this disorder, and homoplasmic mutation in 11778 was detected, thereby confirming the diagnosis of Leber’s hereditary optic neuropathy.